Repeatability of Phase‐Resolved Functional Lung (PREFUL)‐MRI Ventilation and Perfusion Parameters in Healthy Subjects and COPD Patients. Issue 3 (14th October 2020) - Pöhler, Gesa H.; Klimeš, Filip; Behrendt, Lea; Voskrebenzev, Andreas; Gonzalez, Cristian Crisosto; Wacker, Frank; Hohlfeld, Jens M.; Vogel‐Claussen, Jens
Abstract : Background: Free‐breathing phase‐resolved functional lung (PREFUL)‐MRI may be useful for treatment monitoring in chronic obstructive pulmonary disease (COPD) patients with dyspnea. PREFUL test–retest reliability is essential for clinical application. Purpose: To measure the repeatability of PREFUL‐MRI ventilation (V) and perfusion (Q) parameters. Study Type: Retrospective and prospective. Population: A total of 28 COPD patients and 57 healthy subjects. Field Strength/Sequence: 1.5T MRI/2D spoiled gradient echo imaging. Assessment: V and Q lung parameter maps based on three coronal slices were obtained at baseline and after 14 days (COPD patients) or after a short pause outside the scanner (healthy subjects). Regional ventilation (RVent) and imaging flow volume loops by cross‐correlation (ccVent) were quantified. Q was normalized to the signal of the main pulmonary artery (QN ) and quantified (QQuant ). Pulmonary pulse wave transit time (pPTT), voxel‐by‐voxel (regional), and whole lung (global) ventilation defect percentage based on RVent (VDPRVent ) and ccVent (VDPccVent ), perfusion defect percentage (QDP), and ventilation/perfusion match based on RVent (VQMRVent ) and ccVent (VQMccVent ) were calculated. Statistical Tests: Regional V and Q were analyzed globally for each subject. Each parameter's median of scans 1 and 2 were assessed by Wilcoxon sign rank test. A parameter's repeatability was analyzed by Bland–Altman analyses, coefficients of variation, intraclass correlation coefficients (ICC), and power calculations. The regional voxel repeatability was examined by calculating the Sørensen–Dice coefficient. Results: There was no bias and no significant differences between the first and second MRI for any parameters ( P > 0.05). Coefficient of variation ranged from 2.26% (ccVent) to 19.31% (QDP), ICC from 0.93 (QDP) to 0.60 (pPTT), the smallest detectable difference was 0.002 ccVent. Regional comparison showed the highest overlap (84%) in VDPRVent in healthy voxels and the lowest (53%) in VDPccVent defect voxels. Data Conclusion: V and Q PREFUL‐MRI parameters were repeatable over two scan sessions in both healthy controls and COPD patients. Level of Evidence: 2 Technical Efficacy Stage: 2